Aloe-emodin Attenuates Staphylococcus aureus Pathogenicity by Interfering With the Oligomerization of α-Toxin - Jiang, Lanxiang; Yi, Tian; Shen, Ziying; Teng, Zihao; Wang, Jianfeng (Frontiers in Cellular and Infection Microbiology, 2019)
α-toxin, an essential virulence factor secreted by Staphylococcus aureus (S. aureus), is a critical exotoxin in multiple infections. In this study, we found that aloe-emodin (AE), a natural compound lacking anti-S. aureus activity, could inhibit the hemolytic activity of α-toxin. Oligomerization assays, molecular dynamics simulations and fluorescence-quenching analyses were used to determine the mechanism of this inhibition. The oligomerization of α-toxin was restricted by the engagement of AE with K110, T112 and M113 of the toxin, which eventually resulted in inhibition of the hemolytic activity. Lactate dehydrogenase and live/dead assays demonstrated that AE decreased the injury of human lung epithelial cells (A549) and mouse lung macrophages (MH-S) mediated by S. aureus. Furthermore, treatment with AE showed robust protective effects in mice infected by S. aureus. These findings suggest that AE effectively inhibited the pore-forming activity of α-toxin and showed a protective effect against S. aureus virulence in vitro and in vivo, which may provide a new strategy and new antibacterial agent for clinical treatment of S. aureus infections.